E. coli strain-dependent lipid alterations in cocultures with endothelial cells and neutrophils modeling sepsis - Amunugama, Kaushalya; Pike, Daniel P.; Ford, David A. (Frontiers in Physiology, 2022)
Dysregulated lipid metabolism is common in infection and inflammation and is a part of the complex milieu underlying the pathophysiological sequelae of disease. Sepsis is a major cause of mortality and morbidity in the world and is characterized by an exaggerated host response to an infection. Metabolic changes, including alterations in lipid metabolism, likely are important in sepsis pathophysiology. Here, we designed an in vitro cell culture model using endothelial cells, E. coli, and neutrophils to mimic sepsis in a simplified cell model. Lipid alterations were studied in the presence of the pathogenic E. coli strain CFT073 and non-pathogenic E. coli strain JM109. We employed untargeted lipidomics to first identify lipid changes and then targeted lipidomics to confirm changes. Both unique and shared lipid signatures were identified in cocultures with these E. coli strains. In the absence of neutrophils, the CFT073 strain elicited alterations in lysophosphatidylcholine and diglyceride molecular species during coculture while both strains led to increases in phosphatidylglycerols. Lipid alterations in these cocultures changed with the addition of neutrophils. In the presence of neutrophils with E. coli and endothelial cells, triglyceride increases were a unique response to the CFT073 strain while phosphatidylglycerol and diglyceride increases occurred in response to both strains. Phosphatidylethanolamine also increased in neutrophils, E. coli and endothelial cells cocultures, and this response was greater in the presence of the CFT073 strain. We further evaluated changes in phosphatidylethanolamine in a rat model of sepsis, which showed multiple plasma phosphatidylethanolamine molecular species were elevated shortly after the induction of sepsis. Collectively, these findings demonstrate unique lipid responses by co-cultures of E. coli with endothelial cells which are dependent on the E. coli strain as well as the presence of neutrophils. Furthermore, increases in phosphatidylethanolamine levels in CFT073 urosepsis E. coli, endothelial cell, neutrophil cocultures were similarly observed in the plasma of septic rats.